Communication Audit in Eje cafetero private universities (2020)
In the contemporary organizations, communication audit is a supporting task to determinate the existence and effectiveness of communication processes. In that way, the organizational communication systems become in strategic bases in the empower of the companies, where elements such as reputation, image, organizational environment, organizational culture, identity, information management, communication in crisis, social responsibility communication, and all of those intangibles elements are the basement of the company strategy and so that they are susceptible of evaluation.